Pengaruh Relevance, Resonance, dan Reach terhadap Purchase intention Konsumen pada Konten Influencer Teknologi GadgetIn - Jonatan, Kevin; Nur Ramadhan, Mutiara; Saskia, Saskia; Setiawan, Fendi; Maazzallah, Abiil (Universitas Pahlawan Tuanku Tambusai, 2025)
This research aims to examine the impact of three influencer marketing variables, namely Relevance, Resonance, and Reach, on consumer Purchase Intention within the context of digital marketing. The Partial Least Squares Structural Equation Modeling (PLS-SEM) method was employed to process and analyze data collected through an online survey. The analysis revealed that both Relevance and Resonance have a positive and significant impact on Purchase Intention, with path coefficients of 0.467 and 0.290 respectively, while Reach did not show a significant effect. The results emphasize the significance of the quality of relationships and emotional engagement between influencers and their audiences, rather than merely the size of the audience, in driving purchase decisions. This study contributes theoretical insights into the development of the 3R model in influencer marketing and offers practical guidance for industry practitioners to design more effective content strategies